Rene Guenon and his Perennial Philosophy: https://doi.org/10.5281/zenodo.17239637 - Muhammad Iqbal Asif; Prof. Dr. Abdul Quddus Suhaib (`, 2025)
Rene Guenon founded the Traditionalist school. He wrote on different subjects such as metaphysics, symbolism, modern world and traditional sciences. The constant theme of his writings is the sharp contrast between the traditional world view shared by various religions of the world and modernism. In traditional worldview shared by various religions of the world and modern world which contains some of the most profound and enduring analyses of the modern world and its philosophical outlook. In this article, his early days of life, his education, his journey and his contact with spiritual groups and occasional visits with the members of Traditionalist School as Titus Burckhardt, Frithjof Schuon and Martin Lings, his conversion to Islam, his stay in Egypt and devotion to work on his major books and articles., his publication and his work on comparative philosophy and spiritualty and esoterism, his traditional doctrines and his attempt to revive traditional concepts and sciences and his views about Traditional school of thought will be discussed. Keywords: René Guénon, Perennial Philosophy, Traditionalism, Esotericism, Metaphysics